A decision support tool approach based on the Electre TRI-B method for the valorisation of tropical timbers from the Congo Basin: an application for glulam products. Issue 4 (2nd October 2018) - Lissouck, René Oum; Pommier, Régis; Taillandier, Franck; Mvogo, Jean K; Breysse, Denys; Ohandja, Louis M Ayina
Abstract : An alternative approach to the formal management strategy of tropical timber species from the Congo Basin was investigated. It focused on the development of glulam, with an aim to specify a decision support model for the valorisation of tropical timber species considered for use in these products. There were 76 forest species analysed regarding ecological, engineering and social criteria according to their major uses. The Electre TRI-B multicriteria sorting method was used. The main result was a new and robust classification tool of timber species from the Congo Basin, corresponding to their multicriteria consensus degree. The potentials of the new grouping system were analysed. Species that meet a great majority of criteria were identified. They were highly suitable for sustaining the market position of glulam products. Implementing this strategy may significantly improve the management and increase the value of the timber species from the Congo Basin, while preserving endangered species.